Entrepreneurship Education Management Model in Realizing Student Independence at Al-Ittifaq Islamic Boarding School, Bandung Regency - Cici Handritin; Badrudin Badrudin; Hasan Basri; Mursidin Mursidin (International Journal of Islamic Educational Research, 2025)
Entrepreneurship education in Islamic boarding schools to realize the independence of students with the support of various Islamic boarding school economic development programs as a support system. The purpose of this study is to identify the management of entrepreneurship education in realizing the independence of students at the Al-Ittifaq Islamic Boarding School in Bandung, including; 1) Planning, 2) Organization, 3) implementation, 4) evaluation, 5) advantages and disadvantages, 6) Analysis of the Design of an Effective Entrepreneurship Education Management Model. This study uses a qualitative approach using the Ethnography method. Data collection techniques are carried out through interviews, observations and documentation analysis. The data analysis techniques use techniques; data reduction, data presentation and conclusion drawing. While the validity test is carried out using data triangulation and source triangulation techniques. The results of the study found that; First, planning with a deep learning curriculum. Second, the organization has an organized structure according to its duties and functions and the accompanying ustadz according to his entrepreneurial competency. Third, the implementation of entrepreneurship education is carried out with practical mentoring where the ustadz becomes a role model to be followed. Fourth, the evaluation is conducted by providing challenges to students to measure their entrepreneurial abilities practically. Fifth, the advantages are supported by the availability of continuously developed teaching staff, while the disadvantages are obstacles from the mismatch between the desires of students and parents in the educational process. Sixth, an effective Entrepreneurship Education model through entrepreneurship education in Islamic boarding schools and schools, namely the Al Ittifaq Agricultural Vocational School. Seventh, the findings of the SAPUJAGAT Entrepreneurship Education Management model (Santri, Entrepreneur, Soulful, Enthusiastic and Dignified).